The Influence of Caring Training on Nurses' Ability to Manage Patient Complaints in the Intensive Room of SLG Kediri Hospital - Moch. Gandung Satriya; Sri Andarini; Kuswantoro Rusca Putra (Universitas STRADA Indonesia, 2024)
Backgrounds: Satisfaction patient is indicator quality service nursing and success in fulfillment service patient. Standardized service​ already should runs on all units, fine room take care regular, and maintenance units intensive. Purpose: Study this aim for analyze influence caring training towards ability nurse manage complain. Method: Study this using a quantitative design with approach quasy experiment design with group control. Sample size are 21 nurses for every group. Group intervention given based caring training theory swanson. Before and after giving training group intervention will assessed ability nurse manage complain then compared to with group control. Results: Research result show there is significant improvement in implementation​ caring behavior of nurses in manage complain, after get training caring behavior with a mean of 11.38. behavior nurse in give service nursing this is form quality service nursing at home sick that can be influence satisfaction patient. Behavior nurse in give service expected and possible care​ satisfying patient is caring behavior, attention and treatment nurse to client with good. Conclusions: This result expected become reference strategy development for overcome problem related enhancement ability nurse manage complain with consider all over components that influence it in the field nursing.